PALEOCLIMATE RECORD IN BOTTOM SEDIMENTS OF LAKE BAIKAL, FROM MAGNETIC SUSCEPTIBILITY DATA - Krainov M.A.; Kravchinskii V.A.; Peck J.A.; Sakai H.; King J.W.; Kuz'min M.I. (My University, 2001)
Two boreholes on the Akademichesky Ridge, 100 and 200 m deep (BDP-96-1 and BDP-96-2), were drilled and cored continuously as part of the Baikal Drilling Project. Results of low-frequency magnetic susceptibility measurements of the two cores were correlated with the SPECMAP oceanic oxygen isotope curve, and a composite section was compiled. The SPECMAP curve and the magnetic susceptibility of the BDP-96 cores showed a good fit. Frequency analysis of time variations in magnetic susceptibility showed a periodicity of the paleoclimate signal with intervals of 23, 35, 41, 52, 68, 85, 106, and 164 ka. The periods of 23, 41, 52, and 106 ka correspond to cycles of precession, inclination of the Earth's axis, an eccentricity harmonic overlapped with inclination, and the Earth's orbit eccentricity itself, respectively. The periods of 35, 68, and 164 ka, distinguished for the first time in magnetic susceptibility studies but noted earlier in biogenic silica analysis, reflect different eccentricity harmonics, and the period of 68 ka bears an effect of precession. The period of 85 ka has never been revealed before in the climate record and is most likely related to regional periodicity rather than to any astronomic cycles.